In Vivo Study of the Sorbicillinoid Gene Cluster in Trichoderma reesei - Derntl, Christian; Guzmán-Chávez, Fernando; Mello-de-Sousa, Thiago M.; Busse, Hans-Jürgen; Driessen, Arnold J. M.; Mach, Robert L.; Mach-Aigner, Astrid R. (Frontiers in Microbiology, 2017)
Sorbicillinoids are a diverse group of yellow secondary metabolites that are produced by a range of not closely related ascomycetes, including Penicillium chrysogenum, Acremonium chrysogenum, and Trichoderma reesei. They share a similarity to the name-giving compound sorbicillin, a hexaketide. Previously, a conserved gene cluster containing two polyketide synthases has been identified as the source of sorbicillin, and a model for the biosynthesis of sorbicillin in P. chrysogenum has been proposed. In this study, we deleted the major genes of interest of the cluster in T. reesei, namely sor1, sor3, and sor4. Sor1 is the homolog of P. chrysogenum SorA, which is the first polyketide synthase of the proposed biosynthesis pathway. Sor3 is an FAD-dependent monooxygenase, and its homolog in P. chrysogenum, SorC, was shown to oxidize sorbicillin and 2’,3’-dihydrosorbicillin to sorbicillinol and 2’,3’-dihydrosorbicillinol, respectively, in vitro. Sor4 is an FAD/FMN-containing dehydrogenase with an unknown function. We measured the amounts of synthesized sorbicillinoids throughout growth and could verify the roles of Sor1 and Sor3 in vivo in T. reesei. In the absence of Sor4, two compounds annotated to dihydrosorbicillinol accumulate in the supernatant and only small amounts of sorbicillinol are synthesized. Therefore, we suggest extending the current biosynthesis model about Sor4 reducing 2’,3’-dihydrosorbicillin and 2’,3’-dihydrosorbicillinol to sorbicillinol and sorbicillinol, respectively. Sorbicillinol turned out to be the main chemical building block for most sorbicillinoids, including oxosorbicillinol, bisorbicillinol, and bisvertinolon. Further, we detected the sorbicillinol-dependent synthesis of 5-hydroxyvertinolide at early time points, which contradicts previous models for biosynthesis of 5-hydroxyvertinolide. Finally, we investigated if sorbicillinoids from T. reesei have a growth limiting effect on the fungus itself or on plant pathogenic fungi or on pathogenic bacteria.